Primate photopigments and primate color vision. - Jacobs, G H (1996)
The past 15 years have brought much progress in our understanding of several basic features of primate color vision. There has been particular success in cataloging the spectral properties of the cone photopigments found in retinas of a number of primate species and in elucidating the relationship between cone opsin genes and their photopigment products. Direct studies of color vision show that there are several modal patterns of color vision among groupings of primates: (i) Old World monkeys, apes, and humans all enjoy trichromatic color vision, although the former two groups do not seem prone to the polymorphic variations in color vision that are characteristic of people; (ii) most species of New World monkeys are highly polymorphic, with individual animals having any of several types of dichromatic or trichromatic color vision; (iii) less is known about color vision in prosimians, but evidence suggests that at least some diurnal species have dichromatic color vision; and (iv) some nocturnal primates may lack color vision completely. In many cases the photopigments and photopigment gene arrangements underlying these patterns have been revealed and, as a result, hints are emerging about the evolution of color vision among the primates.